A portable solar-powered air-cooling system based on phase-change materials for a vehicle cabin. (15th October 2017) - Qi, Lingfei; Pan, Hongye; Zhu, Xin; Zhang, Xingtian; Salman, Waleed; Zhang, Zutao; Li, Li; Zhu, Miankuan; Yuan, Yanping; Xiang, Bo
Graphical abstract: This paper proposed a portable solar-powered air cooling system for a vehicle cabin based on Phase-change Materials. The cooling system contains three main parts: a solar-energy collection module, an energy-storage module and a phase-change cooling module. The operating principle can be described as follows. For energy input, the solar-energy-collection module harvests solar energy and converts it to electricity. The power-storage module stores the electrical energy in the supercapacitor to power the electrical equipment, mainly the air pump (AP) and water pump (WP) of the phase-change cooling module. Finally, the phase-change cooling module provides cold air for the vehicle cabin to create a comfortable vehicle interior in a hot summer. The proposed system is demonstrated through thermal simulations, which show the long-duration cooling effect of the system. Temperature drops of were obtained in field tests, predicting that the proposed cooling system is beneficial and practical for cooling vehicle cabins. Highlights: A novel portable air cooling system based on PCMs is presented. Solar energy was adopted to power the proposed air cooling system. This proposed system is used for cooling vehicle cabins exposed to the sun. Experimental results show that the proposed system has a good cooling effect. Abstract: In summer, the temperature is very high inside vehicles parked under the hot sun. This causes consuming more fossil energy to power the air conditioner and generation of harmful gases. There is currently no effective method to address this problem in an energy-saving and environmentally friendly manner. In this paper, a novel solar-powered air-cooling system for vehicle cabins is proposed based on Phase-change Materials (PCMs); the system prevents the temperature inside a vehicle cabin from rising too high when the vehicle is parked outdoor exposure to the sun. The proposed system consists of three main parts: a solar-energy collection module, power-storage module and phase-change cooling module. The solar panel converts solar energy into electricity, and the power-storage module stores the electric energy in a supercapacitor that provides power for the phase-change cooling module. Heat exchange between cabin ambient air and the PCMs is conducted in the cooling module to generate cold air. The proposed system is demonstrated through thermal simulations, which show the long-duration cooling effect of the system. Temperature drops of 30 °C were obtained in field tests, predicting that the proposed cooling system is beneficial and practical for cooling vehicle cabins.